Analysis of the Impact of Disruptions from the Launch of Missile on the Stability of a Scanning and Tracking IR Seeker Operation - Daniel GAPIŃSKI (Problemy Mechatroniki)
The paper presents the results of research to determine the impact of disruptions occurring during the launch of missile on the stability of operation of an optoelectronic scanning and tracking IR seeker (homing head). The main task of the seeker is to detect and then precisely track an air target. In the tests, the dynamic disruptions due to overloads acting on the seeker during the launch of the missile system were taken into account. The test results are presented in a graphic form